(untitled) (Transport systems and technologies, 2018)
Augmented Reality is a direct, or indirect view on real physical environment, which elements are augmented by computer calculations. The concept of augmented reality allows a computer to receive information from the environment to preform calculations and display the results in most simple way for a human - in physical space. Augmented reality has many scopes of application, it is used in design, in sports, military purposes, medicine and, of course, in games. The development of augmented reality technology leads to improving user experience, simplifying data input and output. It also makes it possible to use environmental data and augment it with information from external sources. As a result of the study, an application for the mobile iOS operating system was created as a video game with the use of augmented reality and technologies Apple ARKit on the base of 3D engine Unity. Video game clearly demonstrates the capabilities of AR, using a regular smartphone.